Feline Cancer Prevalence in South Africa (1998 – 2005): Contrasts with the Rest of the World - Anthony B. Zambelli (Journal of Basic & Applied Sciences, 2015)
A paucity of information exists on the relative proportions, incidences or outcomes of diagnosis and treatment of feline cancer in South Africa. Standard texts of veterinary oncology quote data from the Northern hemisphere, and geographic differences are apparent. In this retrospective analysis, the electronic medical database of the Onderstepoort Veterinary Academic Hospital was analysed for feline cancer felines admissions for the period 1998 – 2005 (n = 100 out of N = 12,893 feline admissions, or 0.78% of total feline admissions). The average and median age of feline cancer felines was 7 and 9.5 years respectively. In contrast to published reports of US, Australian and European data where lymphosarcoma is the most common cancer affecting cats, squamous cell carcinoma (SCC) forms the predominant neoplasm (48% of all tumours). White or part-white cats were overrepresented in this group, which is consistent with greater ultraviolet light exposure. Lymphoma was the second most common diagnosis, followed by various carcinomas and adenocarcinomas. A large proportion (54%) of felines received some form of treatment.